2001
DOI: 10.1107/s0907444900014578
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of tetragonal lysozyme crystals to changes in relative humidity: implications for post-growth crystal treatments

Abstract: The dynamic response of tetragonal lysozyme crystals to dehydration has been characterized in situ using a combination of X-ray topography, high-resolution diffraction lineshape measurements and conventional crystallographic diffraction. For dehydration from 98% relative humidity (r.h.) to above 89%, mosaicity and diffraction resolution show little change and X-ray topographs remain featureless. Lattice constants decrease rapidly but the lattice-constant distribution within the crystal remains very narrow, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 26 publications
(26 reference statements)
7
49
0
1
Order By: Relevance
“…Dehydration decreases the unit-cell volume and usually has little effect on mosaicity except at large dehydrations (Dobrianov et al, 2001). No evidence of dehydrationinduced cell-volume changes were observed in our control experiment, or for a sample held for 1 h at T = 300 K before irradiation.…”
Section: Methodsmentioning
confidence: 64%
“…Dehydration decreases the unit-cell volume and usually has little effect on mosaicity except at large dehydrations (Dobrianov et al, 2001). No evidence of dehydrationinduced cell-volume changes were observed in our control experiment, or for a sample held for 1 h at T = 300 K before irradiation.…”
Section: Methodsmentioning
confidence: 64%
“…X-ray topography measurements (Tanner, 1976;Fourme et al, 1995;Izumi et al, 1996;Dobrianov et al, 1998Dobrianov et al, , 1999Dobrianov et al, , 2001Otalora et al, 1999;Vidal et al, 1999) were performed on station F-3 by illuminating the entire crystal using a highly parallel (unfocused) monochromatic X-ray beam and recording the diffraction pattern using ®ne-grain high spatial resolution ®lm (Kodak Industrex SR) placed $5 cm from the sample. Under these illumination and detection conditions, every Bragg spot is a unit magni®-cation image of the crystal.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been reported on the dynamic response of tetragonal lysozyme crystals to changes in relative humidity. For example, Dobrianov et al (2001) showed an irreversible unit-cell volume decrease of 9% upon changing the relative humidity around the crystal from 98% to 86%, while Deshpande et al (2005) showed that dehydratation by organic solvents mainly affected the order of the hydrated waters without causing large changes in the unit-cell dimensions. In our control study, where a lysozyme crystal was allowed to dehydrate in air for 15 h, we measured (100 K) a unit cell of a = 77.43 and c = 37.48 Å , which corresponds to a solvent content of 37%.…”
Section: Solvent Content and Crystal Structurementioning
confidence: 99%